2014
DOI: 10.4103/1673-5374.130083
|View full text |Cite
|
Sign up to set email alerts
|

Increased expression of Notch1 in temporal lobe epilepsy: animal models and clinical evidence

Abstract: Temporal lobe epilepsy is associated with astrogliosis. Notch1 signaling can induce astrogliosis in glioma. However, it remains unknown whether Notch1 signaling is involved in the pathogenesis of epilepsy. This study investigated the presence of Notch1, hairy and enhancer of split-1, and glial fibrillary acidic protein in the temporal neocortex and hippocampus of lithium-pilocarpine-treated rats. The presence of Notch1 and hairy and enhancer of split-1 was also explored in brain tissues of patients with intrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 65 publications
1
5
0
Order By: Relevance
“…Notch signalling plays an important role in the neuroinflammation and neuronal damage in TLE [27]. Numerous studies have demonstrated that Notch signalling is activated in both TLE model rats and humans with TLE [18, 19]. Consistent with previous studies, we found that the expression of Notch-1 and its downstream target gene Hes-1 were significantly higher in the model group than in the control group.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Notch signalling plays an important role in the neuroinflammation and neuronal damage in TLE [27]. Numerous studies have demonstrated that Notch signalling is activated in both TLE model rats and humans with TLE [18, 19]. Consistent with previous studies, we found that the expression of Notch-1 and its downstream target gene Hes-1 were significantly higher in the model group than in the control group.…”
Section: Discussionsupporting
confidence: 90%
“…It has been shown that Notch signalling is up-regulated in TLE mice and activation of Notch signalling further promotes the excitation of CA1 pyramidal neurons in acute seizures [18]. Notch-1 and hairy and enhancer of split 1 (Hes 1) are up-regulated in the temporal neocortex of patients with intractable TLE [19]. However, the regulatory mechanisms underlying the effects of miRNA-146a in Notch signalling remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, zileuton was shown to decrease spike-wave discharges in pilocarpine epileptic rats [168], strongly suggesting that leukotrienes play a role in epilepsy.…”
Section: Cerebral Localization Of Cyslt Receptorsmentioning
confidence: 99%
“…Pharmacological inhibition of LOX using dual inhibitors of LOX/COX pathway phenidone [ 160 , 166 ], which decreased the production of CysLTs, or BW755C [ 167 ] attenuated the seizure activity. Similarly, zileuton was shown to decrease spike-wave discharges in pilocarpine epileptic rats [ 168 ], strongly suggesting that leukotrienes play a role in epilepsy.…”
Section: Cerebral Localization Of Cyslt Receptorsmentioning
confidence: 99%
“…Changes of Notch 1 receptor have been shown in the animal model of temporal lobe epilepsy as well as absence epilepsy in the WAG/Rij rats. (X. Liu, Yang, Yin, & Deng, ; Sha et al, ).…”
Section: Introductionmentioning
confidence: 99%